Natural Compaction of Semarang-Demak Alluvial Plain and Its Relationship to the Present Land Subsidence - Sarah, Dwi; Hutasoit, Lambok M; Delinom, Robert M; Sadisun, Imam A (Geological Agency, 2020)
DOI:10.17014/ijog.7.3.273-289Land subsidence is the lowering of ground surface due to natural and/or anthropogenic processes. Land subsidence in the Semarang-Demak plain has been going on for more than thirty years, however the contribution of natural and anthropogenic causes is relatively unknown. The Semarang-Demak plain has only been formed recently, as a result of rapid sedimentation during the Holocene. The basin mainly consists of underconsolidated thick clay, vulnerable to excessive settlement due to its own weight and additional pressures. The rate of natural subsidence is quantified by modelling the delayed dissipation of measured overpressure and the resulting vertical deformation, resulting in natural compaction rate of less than 0.8 cm/year in Semarang City and more than 0.8 cm/year in Demak Regency. The subsidence computed for parts of the Semarang-Demak plain were compared to the measured geodetic rate, and the relative contributions of natural and anthropogenic causes are derived. Modelling results show that natural subsidence is more significant at the eastern part of the plain (Demak region) with compaction rate reaching 0.9 - 2.2 cm/year that counts for 48 - 92% of the total land subsidence.